Geothermal Energy As An Alternative Source For Indonesia’s Energy Security: The Prospect And Challenges - Sahdarani, D.N.; Ponka, M.A.; Oktaviani, A.D. (UI Scholars Hub, 2020)
Geothermal energy is a naturally occurring energy resource widely distributed in Indonesia. By 2025, the Indonesian government is expecting a rise in renewable energy installations to supply energy demand within the country. With 1,945 MW of installed capacity reported in 2017, the electricity production from geothermal power plant are expected to meet such electricity demand. Indonesia holds a large potential in geothermal energy with the possibility to meet the energy demand due to population growth. However, geothermal energy faces a challenge when competing with national LCOE. The role of government to create policy and stakeholder to provide technical aids are vital to attract investors to develop environmentally friendly and sustainable geothermal energy.